2014
DOI: 10.1111/ijsa.12063
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Measurement Equivalence of Online Selection Assessments Delivered on Mobile versus Nonmobile Devices

Abstract: Recent usage data suggest job applicants are completing online selection assessments using mobile devices (e.g., smartphones) in greater numbers. To determine the appropriateness of this new technology, this study examined the measurement equivalence of selection assessments delivered on mobile and nonmobile devices (e.g., personal computers). Measurement invariance tests conducted with multigroup confirmatory factor analysis suggest mobile versions of a cognitive ability‐type assessment, two biodata assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 59 publications
3
34
0
1
Order By: Relevance
“…This is an important difference since prior research has shown that the user interface can have an impact on computer and web-based test scores (Bridgeman, Lennon, & Jackenthal, 2003;Huff, Cline, & Guynes, 2012;Květon, Jelínek, Vobořil, & Klimusová, 2007;Schroeders and Wilhelm, 2010;Wästlund et al's, 2008). More specifically to this research, very recent research have found differences in mean test scores between mobile devices and traditional computers (Arthur et al, 2014;Illingworth et al, 2014;Morelli et al, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010). However, the effect sizes of those differences have traditionally been small and very little is known as to why the differences exist at all.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…This is an important difference since prior research has shown that the user interface can have an impact on computer and web-based test scores (Bridgeman, Lennon, & Jackenthal, 2003;Huff, Cline, & Guynes, 2012;Květon, Jelínek, Vobořil, & Klimusová, 2007;Schroeders and Wilhelm, 2010;Wästlund et al's, 2008). More specifically to this research, very recent research have found differences in mean test scores between mobile devices and traditional computers (Arthur et al, 2014;Illingworth et al, 2014;Morelli et al, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010). However, the effect sizes of those differences have traditionally been small and very little is known as to why the differences exist at all.…”
Section: Introductionmentioning
confidence: 92%
“…What research that does exists (Arthur, Doverspike, Muñoz, Taylor, & Carr, 2014;Illingworth, Morelli, Scott, & Boyd, 2014;Morelli, Mahan, & Illingworth, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010) demonstrates that assessments can be impacted by the type of device that was used to completed it and that this impact is not necessarily consistent across different types of assessments. What little we know about the differences that exist is limited by the lack of experiments investigating issues that may cause differences on assessments across devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amennyiben a pedagógiai adatfelvétel a számítógépek valamelyik fajtáján történik (pl. Schröders és Wilhelm, 2010;Morelli, Mahan és Illingworth, 2014), számítógépes mérés-értékelés (computerised, computer-based testing/assessment) valósul meg. A számítógépes tesztelés során a teljes teszt vagy a megoldandó item(ek) a számítógép képernyőjén jelenik/jelennek meg és a diák billentyűzet vagy egér használatával adja meg válaszát (Csapó és mtsai, 2008).…”
Section: A Technológia Alapú Mérés-értékelés Fajtáiunclassified